Prove that trigonometric equation $\dfrac{\tan \theta }{\sec \theta +1}=\dfrac{\sec \theta -1}{\tan \theta }$.
Answer
Verified
510k+ views
Hint: The given question is related to trigonometric identities. Try to recall the formulae related to the relationship between sine, cosine, tangent, and secant of an angle.
Complete step-by-step answer:
Before proceeding with the problem, first, let’s see the formulae used to solve the given problem.
$\tan \theta =\dfrac{\sin \theta }{\cos \theta }$
$\sec \theta =\dfrac{1}{\cos \theta }$
$1-{{\cos }^{2}}\theta ={{\sin }^{2}}\theta $
We need to prove that $\dfrac{\tan \theta }{\sec \theta +1}=\dfrac{\sec \theta -1}{\tan \theta }$.
First, we will consider the left-hand side of the equation. The left-hand side of the equation is given as $\dfrac{\tan \theta }{\sec \theta +1}$ . We know $\tan \theta =\dfrac{\sin \theta }{\cos \theta }$ and $\sec \theta =\dfrac{1}{\cos \theta }$ . So, the left-hand side of the equation becomes $\dfrac{\dfrac{\sin \theta }{\cos \theta }}{\dfrac{1}{\cos \theta }+1}$ .
$\Rightarrow LHS=\dfrac{\dfrac{\sin \theta }{\cos \theta }}{\dfrac{1+\cos \theta }{\cos \theta }}$
$\Rightarrow LHS=\dfrac{\sin \theta }{1+\cos \theta }$
Now, we know that the value of a fraction does not change on multiplying and dividing the fraction by the same number, except $0$ .
So, $LHS=\dfrac{\sin \theta }{1+\cos \theta }\times \dfrac{1-\cos \theta }{1-\cos \theta }$ .
$\Rightarrow LHS=\dfrac{\sin \theta \left( 1-\cos \theta \right)}{1-{{\cos }^{2}}\theta }$
Now, we know that the value of $1-{{\cos }^{2}}\theta $ is equal to ${{\sin }^{2}}\theta $. So, the value of the left-hand side of the equation becomes $\dfrac{\sin \theta \left( 1-\cos \theta \right)}{{{\sin }^{2}}\theta }$ .
$\Rightarrow LHS=\dfrac{1-\cos \theta }{\sin \theta }$
So, the value of the left-hand side of the equation is equal to $\dfrac{1-\cos \theta }{\sin \theta }$ .
Now, we will consider the right-hand side of the equation. The right-hand side of the equation is given as $\dfrac{\sec \theta -1}{\tan \theta }$ . We know $\tan \theta =\dfrac{\sin \theta }{\cos \theta }$ and $\sec \theta =\dfrac{1}{\cos \theta }$ . So, the right-hand side of the equation becomes $\dfrac{\dfrac{1}{\cos \theta }-1}{\dfrac{\sin \theta }{\cos \theta }}$ .
\[\Rightarrow RHS=\dfrac{\dfrac{1-\cos \theta }{\cos \theta }}{\dfrac{\sin \theta }{\cos \theta }}\]
$\Rightarrow RHS=\dfrac{1-\cos \theta }{\sin \theta }$
So, the value of the right-hand side of the equation is equal to $\dfrac{1-\cos \theta }{\sin \theta }$ . Clearly, the values of the left-hand side of the equation and the right-hand side of the equation are the same, i.e. LHS=RHS. Hence, proved.
Note: Students generally get confused and write $1+{{\cos }^{2}}\theta ={{\sin }^{2}}\theta $ instead of $1-{{\cos }^{2}}\theta ={{\sin }^{2}}\theta $ , which is wrong. These formulae should be properly remembered without any mistake as confusion in the formula can result in getting a wrong answer.
Complete step-by-step answer:
Before proceeding with the problem, first, let’s see the formulae used to solve the given problem.
$\tan \theta =\dfrac{\sin \theta }{\cos \theta }$
$\sec \theta =\dfrac{1}{\cos \theta }$
$1-{{\cos }^{2}}\theta ={{\sin }^{2}}\theta $
We need to prove that $\dfrac{\tan \theta }{\sec \theta +1}=\dfrac{\sec \theta -1}{\tan \theta }$.
First, we will consider the left-hand side of the equation. The left-hand side of the equation is given as $\dfrac{\tan \theta }{\sec \theta +1}$ . We know $\tan \theta =\dfrac{\sin \theta }{\cos \theta }$ and $\sec \theta =\dfrac{1}{\cos \theta }$ . So, the left-hand side of the equation becomes $\dfrac{\dfrac{\sin \theta }{\cos \theta }}{\dfrac{1}{\cos \theta }+1}$ .
$\Rightarrow LHS=\dfrac{\dfrac{\sin \theta }{\cos \theta }}{\dfrac{1+\cos \theta }{\cos \theta }}$
$\Rightarrow LHS=\dfrac{\sin \theta }{1+\cos \theta }$
Now, we know that the value of a fraction does not change on multiplying and dividing the fraction by the same number, except $0$ .
So, $LHS=\dfrac{\sin \theta }{1+\cos \theta }\times \dfrac{1-\cos \theta }{1-\cos \theta }$ .
$\Rightarrow LHS=\dfrac{\sin \theta \left( 1-\cos \theta \right)}{1-{{\cos }^{2}}\theta }$
Now, we know that the value of $1-{{\cos }^{2}}\theta $ is equal to ${{\sin }^{2}}\theta $. So, the value of the left-hand side of the equation becomes $\dfrac{\sin \theta \left( 1-\cos \theta \right)}{{{\sin }^{2}}\theta }$ .
$\Rightarrow LHS=\dfrac{1-\cos \theta }{\sin \theta }$
So, the value of the left-hand side of the equation is equal to $\dfrac{1-\cos \theta }{\sin \theta }$ .
Now, we will consider the right-hand side of the equation. The right-hand side of the equation is given as $\dfrac{\sec \theta -1}{\tan \theta }$ . We know $\tan \theta =\dfrac{\sin \theta }{\cos \theta }$ and $\sec \theta =\dfrac{1}{\cos \theta }$ . So, the right-hand side of the equation becomes $\dfrac{\dfrac{1}{\cos \theta }-1}{\dfrac{\sin \theta }{\cos \theta }}$ .
\[\Rightarrow RHS=\dfrac{\dfrac{1-\cos \theta }{\cos \theta }}{\dfrac{\sin \theta }{\cos \theta }}\]
$\Rightarrow RHS=\dfrac{1-\cos \theta }{\sin \theta }$
So, the value of the right-hand side of the equation is equal to $\dfrac{1-\cos \theta }{\sin \theta }$ . Clearly, the values of the left-hand side of the equation and the right-hand side of the equation are the same, i.e. LHS=RHS. Hence, proved.
Note: Students generally get confused and write $1+{{\cos }^{2}}\theta ={{\sin }^{2}}\theta $ instead of $1-{{\cos }^{2}}\theta ={{\sin }^{2}}\theta $ , which is wrong. These formulae should be properly remembered without any mistake as confusion in the formula can result in getting a wrong answer.
Recently Updated Pages
Master Class 11 Accountancy: Engaging Questions & Answers for Success
Glucose when reduced with HI and red Phosphorus gives class 11 chemistry CBSE
The highest possible oxidation states of Uranium and class 11 chemistry CBSE
Find the value of x if the mode of the following data class 11 maths CBSE
Which of the following can be used in the Friedel Crafts class 11 chemistry CBSE
A sphere of mass 40 kg is attracted by a second sphere class 11 physics CBSE
Trending doubts
Define least count of vernier callipers How do you class 11 physics CBSE
The combining capacity of an element is known as i class 11 chemistry CBSE
Proton was discovered by A Thomson B Rutherford C Chadwick class 11 chemistry CBSE
Find the image of the point 38 about the line x+3y class 11 maths CBSE
Can anyone list 10 advantages and disadvantages of friction
Distinguish between Mitosis and Meiosis class 11 biology CBSE